Application of endobronchial ultrasonography in laparoscopic liver segmentectomy in an animal model. Issue 2 (May 2017) - Abe, Tomoyuki; Kobayashi, Tsuyoshi; Shimizu, Seiichi; Hamaoka, Michinori; Iwako, Hiroshi; Hashimoto, Masakazu; Mikuriya, Yoshihiro; Kuroda, Shintaro; Tashiro, Hirotaka; Ohdan, Hideki
Abstract: Introduction: This study investigated whether laparoscopic ultrasound‐guided segment staining and real‐time ultrasound‐guided hepatectomy, with endobronchial ultrasonography equipped with a guide sheath, would be useful for laparoscopic liver segmentectomy in a porcine model. Material and Surgical Technique: The abdominal cavity (in two pigs) was reached via a 12‐mm umbilical trocar. An artificial tumor was created by radiofrequency ablation within the intended resection area. Portal vein puncture and staining were performed by the endobronchial ultrasonography‐guided method. The targeted portal branch was successfully visualized and punctured with a needle through an equipped guide sheath. After targeted segment staining, the liver parenchyma was resected with a bipolar energy device; the regional Glisson's sheath was ligated and cut, and a surgical specimen was extracted. Real‐time endobronchial ultrasonography from the cut surface provided information vital for preserving the surgical margin. All procedures were performed laparoscopically. Discussion: This study demonstrated the technical feasibility of laparoscopic ultrasound‐guided portal vein staining and safe surgical resection during laparoscopic liver segmentectomy.